Effect of Total Macroscopical Sampling of the Pediatric Appendectomy Specimen on Histopathological Diagnosis: EVALUATION OF PEDIATRIC APPENDECTOMY SPECIMEN - Cakir, Ebru; Oztan, Mustafa Onur; Abdullazade, Samir; Ekmekci, Sumeyye; Koyluoglu, Gokhan (Iranian Journal of Pediatric Surgery, 2021)
Introduction: Acute appendicitis is considered the most common abdominal surgery in children. Pathological examination of the appendectomy specimen mainly is performed to document the presence or absence of inflammation and confirm the clinical diagnosis. If the diagnosis made by the pathologist is as ‘no appendicitis’, then clinical work up for other causes should be performed. Routine macroscopic evaluation of the appendectomy specimen consists of obtaining one section each from the base, body and the tip of the appendix and additional sections obtained from exuding or perforated areas. The aim of this study is to evaluate if the final pathological diagnosis would change when the appendectomy specimen is sampled totally. Materials and Methods: In the present study, we performed conventional macroscopical sampling from the tip, body and base of the appendix and embedded these tissues in the first two cassettes, then the rest of appendix was completely sampled in additional two to five casettes. The histopathological diagnosis of conventionally sampled tissues and the histopathological diagnosis of total macroscopical sampling were analyzed and compared. Results: A total of 87 appendectomies were evaluated, of which 58.6 % were male, and the mean age was 11.7 (1 years-18 years). The initial histopathological diagnosis was changed in 14 (16%) cases. In 8 (9.2%) cases, the initial diagnosis of reactive lymphoid hyperplasia changed to acute focal appendicitis (early appendicitis). In 4 (4.6%) cases the initial diagnosis of acute suppurative appendicitis changed to acute suppurative and perforated appendicitis, and in 2 (2.2%) cases acute perforated appendicitis changed to acute perforated and gangrenous appendicitis. Conclusion: Total macroscopical sampling of the appendectomy specimen in cases of negative appendicitis would improve the diagnosis and can document early appendicitis in pediatric cases.